Predictive ability of a laboratory performance test in mountain bike cross-country Olympic athletes - Schneeweiss, P.; Schellhorn, P.; Haigis, D.; Niess, A.; Martus, P.; Krauss, I. (International Journal of Sports Medicine, 2019)
Mountain bike Cross-Country Olympic (XCO) has an intermittent performance profile, underlining the importance of anaerobic metabolism. Traditional performance tests in cycling primarily quantify aerobic metabolism and inadequately meet the demands in XCO. The aim was therefore to validate a specific test that quantifies these requirements by means of an XCO race.